Social Determinants of Health Associated With the Development of Sepsis in Adults: A Scoping Review. (15th July 2022) - Sheikh, Fatima; Douglas, William; Catenacci, Vanessa; Machon, Christina; Fox-Robichaud, Alison E.
Abstract : OBJECTIVE: Evaluating risk for sepsis is complicated due to limited understanding of how social determinants of health (SDoH) influence the occurence of the disease. This scoping review aims to identify gaps and summarize the existing literature on SDoH and the development of sepsis in adults. DATA SOURCES: A literature search using key terms related to sepsis and SDoH was conducted using Medline and PubMed. STUDY SELECTION: Studies were screened by title and abstract and then full text in duplicate. Articles were eligible for inclusion if they: 1) evaluated at least one SDoH on the development of sepsis, 2) participants were 18 years or older, and 3) the studies were written in English between January 1970 and January 2022. Systematic reviews, meta-analyses, editorials, letters, commentaries, and studies with nonhuman participants were excluded. DATA EXTRACTION: Data were extracted in duplicate using a standardized data extraction form. Studies were grouped into five categories according to the SDoH they evaluated (race, socioeconomic status [SES], old age and frailty, health behaviors, and social support). The study characteristics, key outcomes related to incidence of sepsis, mortality, and summary statements were included in tables. DATA SYNTHESIS: The search identified 637 abstracts, 20 of which were included after full-text screening. Studies evaluating SES, old age, frailty, and gender demonstrated an association between sepsis incidence and the SDoH. Studies that examined race demonstrated conflicting conclusions as to whether Black or White patients were at increased risk of sepsis. Overall, a major limitation of this analysis was the methodological heterogeneity between studies. CONCLUSIONS: There is evidence to suggest that SDoH impacts sepsis incidence, particularly SES, gender, old age, and frailty. Future prospective cohort studies that use standardized methods to collect SDoH data, particularly race-based data, are needed to inform public health efforts to reduce the incidence of sepsis and help clinicians identify the populations most at risk.